Archaeological excavations at Gradina sv. Ivana on the island of Korčula (In situ, 2024)
The paper presents the preliminary results of the second season of the archaeological research at Gradina svetog Ivana on the western part of the island of Korčula. Three new trial trenches opened at critical positions of the site confirmed its occupation during the Middle Bronze Age, Late Antiquity and the Modern Era. A great novelty was presented by the burial from the 11th/12th century, opening up the possibility of the existence of an early medieval phase of the church of St. John, initially an early Christian structure, also with a late medieval phase.
Keywords: Korčula; Gradina svetog Ivana; Bronze Age; Late Antiquity; Middle Age; Modern Era